PENGEMBANGAN FORMAT PENILAIAN HASIL BELAJAR SISWA PADA KURIKULUM 2013 SEKOLAH MENENGAH PERTAMAKOTA PADANG - Novrianti Novrianti; Zuliarni Zuliarni (E-Tech : Jurnal Ilmiah Teknologi Pendidikan, 2021)
This research is based on the problems that exist in curriculum changes, with changes in the curriculum of course also bringing changes to the student learning outcomes assessment system that will be used later. The many assessment formats that must be carried out in the 2013 curriculum, require extra work each time the exam if this is done manually. This of course will take a lot of time for the teacher to do the assessment. So it requires an application to conduct an assessment. Because the duties and obligations of teachers are so many, one of which is to conduct an assessment. This study aims to develop and measure the level of validity and practicality of the student learning outcomes assessment format. This type of research is development research known as Research and Development (R&D). This study uses the Borg and Gall development model. The development of this research procedure consists of four stages, namely stage of informationgathering, planning, early product development stage, field testing, revision and final products. The product validity test was carried out by three validators, namely one content validator and two media validators. The product trial was conducted on 4 teachers from each school, namely SMP Laboratorium UNP, SMPN 4 Padang and SMPN 29 Padang, by collecting data from each respondent using a questionnaire. This development research resulted in a product in the form of alearning outcome assessment format Compact Disk (CD). This research has been tested and is feasible to be developed. The results of data analysis show that the assessment format has a content validity level of 3.9, while media validation is 4.6. In terms of practicality has been declared practical by the respondents that is equal to 4.22. Based on the data obtained, it can be concluded that the assessment format can be used in assessing learning outcomes for schools that have used thecurriculum 2013.Keywords: Development, Assessment Format, Learning Outcomes, 2013 Curriculum